Analisa biaya pengembangan objek wisata air di perairan Sungai Siak bagi masyarakat Rumbai Pesisir Pekanbaru - Joko Risanto (Unri Conference Series: Community Engagement, 2020)
Ekowisata is a regional environmental (ecological) based tourism development. The coast of the Siak River is an area that has the potential to attract tourism and at the same time improve the economy of local communities. A strategy is needed to motivate the public and business actors to take an active role in the tourism industry. Investors have to consider the costs and benefits of investing. The community also has limited capital to do business. So in this research activity the team divides the development strategy into three targets, namely the first target is to increase public interest through small and medium enterprises, the second is to provide encouragement to local governments, namely the sub-district (kelurahan) to prepare groups of middle economic actors and the third is to provide opportunities for investors. to manage the water tourism industry in collaboration with the community. One form of the community's active role is to invite them to build tourist icons on the coast of the Siak River and provide training in making Malay culinary.